Interactive E-Book Learning Media Based on Project Based Learning on Mathematics Content Multiplication Material in Grade V Elementary School - I Dewa Ayu Mas Gita Pramesti; I Wayan Wiarta; Dewi Anzelina (Jurnal Ilmiah Sekolah Dasar, 2025)
The lack of contextual learning and the use of unengaging media in elementary school mathematics often result in low conceptual understanding and reduced student motivation, especially in multiplication, thus failing to meet the expected competency standards. This study aims to develop, assess the feasibility, and effectiveness of an interactive e-book based on Project Based Learning. This is a research and development (R&D) study using the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). The research subjects included experts in product design, subject matter, instructional design, learning media, and 28 fifth-grade students. The instruments used were questionnaires and tests, with data analysis techniques involving quantitative descriptive, qualitative descriptive, and inferential statistics. The feasibility results showed scores ranging from 86.11%-96.60%, classified as good to very good. The t-test showed tcalculated>ttable (10.883>1.703), indicating that H0 was rejected and H1 was accepted. In conclusion, the interactive e-book based on Project Based Learning is proven to be feasible, effective, and capable of improving students’ understanding and learning outcomes. This media can serve as an innovative alternative to support teachers in creating engaging, interactive, and contextual learning.